Refugee-background students and the institutional responsibility of schools: a narrative discourse analysis of US education news media. Issue 2 (4th March 2023) - Warren, Amber N.; Karam, Fares J.; Ward, Natalia
ABSTRACT: Necessitated by a heightened focus on global migration and its impact on educational realities across the globe, this study examined how educational experiences of students with refugee backgrounds are characterized in US educational news outlets. 385 articles from three online education news sites in the US were examined using a narrative-discursive approach. Analysis demonstrated how mutually dependent narrative patterns constructed students as resilient survivors, while schools were positioned as safe havens designed to support them. We show how these narrative patterns were accomplished through the use of common discursive features, positioning refugee student populations and the institutional responsibility of schools in bounded ways. We consider these findings in light of how broader discourses visible in news media narratives shape and reflect the reality of refugee-background students' educational experiences in the US.